The adoption and impacts of improved parboiling technology for rice value chain upgrading on the livelihood of women rice parboilers in Benin - Arouna, Aminou; Aboudou, Rachidi; Ndindeng, Sali Atanga (Frontiers in Sustainable Food Systems, 2023)
Food insecurity and child malnutrition remain persistent problems in sub-Saharan Africa. Rice is a staple food for more than half of the world’s population. However, white rice is poor in micronutrients and records higher glycemic values compared to parboiled rice. An improved parboiling system called “Grain quality enhancer, Energy-efficient and durable Material” (GEM in short) allows the processing of quality rice with better physical and nutritional properties compared to traditional systems. This paper assessed the drivers and impact of the adoption of the GEM system on women’s livelihoods. A total of 822 rice women parboilers were randomly sampled and interviewed in Benin, in regions where the GEM system was introduced. We employed the endogenous switching regression model (ESR) to assess the impact of the GEM system. We found evidence that adoption of the GEM system increased women parboilers’ rice output rate (dehulling return), income and food security and reduced poverty. The impact of the GEM system is estimated at 14.38 kg of milled rice per 100 kg of paddy (21.46%), equivalent to US$ 7.25 of additional income (17.77%). A significantly lower poverty rate of 26% was found among households due to the adoption of the GEM system. These results are supported by women’s perceptions that the output rate, better nutritional value and reduction of broken rice during dehulling are major advantages of the improved parboiling system. Policy actions such as training of local fabricators and credit options are required for out-scaling and sustainability of the improved parboiling system.